Hsp47 Inhibitor Col003 Attenuates Collagen-Induced Platelet Activation and Cerebral Ischemic–Reperfusion Injury in Rats - Wu, Shuang; Liang, Chengwei; Xie, Xiaoyun; Huang, Haiping; Fu, Jinfeng; Wang, Cilan; Su, Zhiheng; Wang, Youqiong; Qu, Xiang; Li, Jinpin; Liu, Jingli (Frontiers in Pharmacology, 2022)
Ischemic stroke is a major type of stroke worldwide currently without effective treatment, although antiplatelet therapy is an existing option for it. In previous studies, heat shock protein 47 (Hsp47) was found to be expressed on the surface of human and mice platelets and to strengthen the interaction between platelets and collagen. In recent years, Col003 was discovered to inhibit the interaction of Hsp47 with collagen. We evaluated whether the Hsp47 inhibitor Col003 is a promising therapeutic agent for ischemic stroke. Here, we first verified that Hsp47 is also expressed on the surface of rat platelets, and its inhibitor Col003 significantly inhibited thrombus formation in the FeCl3-induced rat carotid arterial thrombus model. Both Col003 and clopidogrel did not alter the bleeding time or coagulation parameters, while aspirin increased the tail-bleeding time (P < 0.05). The low cytotoxicity level of Col003 to rat platelets and human liver cells was similar to those of aspirin and clopidogrel. Col003 inhibited collagen-induced platelet aggregation, adhesion, [Ca2+]i mobilization, P-selectin expression, ROS production and the downstream signal pathway of collagen receptors. The results of the middle cerebral artery occlusion (MCAO) model indicated that Col003 has a protective effect against cerebral ischemic–reperfusion injury in rats. The Hsp47 inhibitor Col003 exerted antiplatelet effect and protective effect against brain damage induced by ischemic stroke through the inhibition of glycoprotein VI (GPVI)and mitogen-activated protein kinase (MAPK) signaling events, which might yield a new antiplatelet agent and strategy to treat ischemic stroke.